The Evidence for the Production Mechanism of cis-S-1-Propenylcysteine in Aged Garlic Extract Based on a Model Reaction Approach Using Its Isomers and Deuterated Solvents - Kodera, Yukihiro; Matsutomo, Toshiaki; Itoh, Kenji (Planta Medica Letters, 2015)
cis-S-1-Propenylcysteine has been identified in aged garlic extract, however, its production mechanism is still unclear. The content of cis-S-1-propenylcysteine in aged garlic extract at 22 months of aging was more than twice the molarity of γ-glutamyl-cis-S-1-propenylcysteine in raw garlic, a plausible precursor of cis-S-1-propenylcysteine. We found that cis-S-1-propenylcysteine was generated through the isomerization of trans-S-1-propenylcysteine in the model reactions. These results suggested that the isomerization was induced by the electron-releasing conjugative effect of the sulfur atom in S-1-propenylcysteine.
Keywords: Allium sativum; Amaryllidaceae; aged garlic extract; isomerization; cis/trans-S-1-propenylcysteine